Fuel behavior analysis code FEMAXI-FBR development and validation for core disruptive accident. (July 2015) - Okawa, T.; Tatewaki, I.; Ishizu, T.; Endo, H.; Tsuboi, Y.; Saitou, H.
Abstract: Japan Nuclear Energy Safety Organization (JNES) is a Technical Safety Organization (TSO) for Japanese Nuclear Regulation Authority to provide technical information on safety reviews including incident and accident analyses of nuclear power plants including Fast Breeder Reactor (FBR). JNES has developed an ASTERIA-FBR code system as an integrated Core Disruptive Accident (CDA) analysis code of the regulatory side for the purpose of evaluating the Unprotected Loss-of-Flow (ULOF) accident of FBR cores. The ASTERIA-FBR consists of three main modules, a thermal-hydraulics calculation module; CONCORD, a fuel behavior calculation module; FEMAXI-FBR, and a neutronic calculation module; dynamic GMVP. The FEMAXI-FBR is based on a LWR fuel behavior simulation code FEMAXI-6 and modified the material properties, the calculation models for steady state and transient operational conditions. The FEMAXI-FBR has been validated by French CABRI slow-TOP (E12) and fast-TOP (BI2) transient test data. Furthermore, the fuel temperature calculation model was validated by B5D Power-To-Melt (PTM) test at the experimental fast reactor JOYO in Japan. Through these validation, the code is found to be capable of evaluating FBR fuel pin behavior from normal to accidental conditions precisely.